Stable weak shadowable symplectomorphisms are partially hyperbolic - Bessa, Mário (2014)
Let M be a closed, symplectic connected Riemannian mani- fold and f a symplectomorphism on M. We prove that if f is C1-stably weak shadowable on M, then the whole manifold M admits a partially hyperbolic splitting.